The Isosceles Nasal Tip—Laser-Assisted Midline Assessment in Rhinoplasty - Neves, Jose Carlos; Rivero, Irene (Facial Plastic Surgery, 2024)
The accurate determination of the nasal tip's spatial location is crucial for achieving symmetry in rhinoplasty. Even minor deviations can result in asymmetrical lengths and configurations of the nostrils. Our approach centers on defining the nasal tip position by establishing the midline of the nasal base and projecting an isosceles triangle. This triangle, with the tip as the vertex and alar creases as angles, ensures symmetric sidewalls. The symmetry axis, derived from the isosceles triangle, guides the placement of the tip sidewalls and columella. To implement this, we use anatomical benchmarks such as the implantation of the nasal base and position of the alar creases, considering inherent facial asymmetries. We introduce a laser gadget as an auxiliary tool, projecting perpendicular lines to guide precise midline alignment. Marking specific points, including interbrow midpoint and alar creases, ensures accuracy. In the past 12 months, we applied this methodology in 247 rhinoplasty cases, observing improved outcomes and patient satisfaction. Our proposal of utilizing isosceles triangles provides a streamlined approach to achieving symmetry. The laser device, while beneficial, should be viewed as supportive rather than an absolute guiding measure.
Keywords: rhinoplasty; laser-assisted rhinoplasty; facial asymmetry; nose; isosceles; tip